Evaluación económica de un sistema silvo-apícola-pastoril en el norte continental de la provincia de Buenos Aires - Alvarez Barreto, V.; Cabrini, Silvina María; Fillat, Francisco Antonio; Ferrere, Paula; Signorelli, Alejandro Gabriel (CIPAV, 2023)
The objective of this study was to make an economic evaluation of a silvo-beekeeping-pastoral system (SSAP) in the continental North of the province of Buenos Aires. A private cost-benefit analysis of an SSAP was performed for a producer who decides to incorporate afforestation with poplar trees and beehives to his livestock production system, and a private cost-benefit analysis at the regional level of an alternative scenario in which each livestock farm with more than 1000 head of cattle forests 100 hectares with poplar, and produce honey in association with a beekeeper. The NPV calculated for this SSAP was 3295 u$s.ha-1 and 3015 u$s.ha-1 with and without the current subsidies for forestation, respectively. For the baseline scenario, the livestock production NPV was 3861 U$S.ha-1 . With a premium of 35% to the value of the meat of the SSAP by certification "carbon neutral meat" the NPVs are equated. At the regional level, the greatest impacts of the alternative scenario are in the forested area and number of hives. The surface with forage is maintained, but a percentage becomes under shade. The NPV of the SSAP was 329,463 u$s.establishment-1 (100 ha) and 95,214,681 u$s.region-1 (289 establishments). The results indicate that, when contributions from subsidies and a premium for low carbon meat are considered, SSAP becomes an economically viable alternative to consider in the area.